A novel approach for producing Mg-3Al-1Zn-0.2Mn alloy wire with a promising combination of strength and ductility using CoreFlowTM. (1st April 2023) - Zhao, Xingjian; Zeng, Xun; Yuan, Liang; Gandra, Joao; Hayat, Qamar; Bai, Mingwen; Rainforth, W Mark; Guan, Dikai
Abstract: Mg-3Al-1Zn-0.2Mn (wt.%, AZ31B) wires were successfully produced from commercial hot-rolled plates in one step using the CoreFlow TM process, a novel stationary shoulder friction stir extrusion manufacturing. CoreFlowed AZ31B wires exhibited fine grains with a heterogeneous grain size distribution of 6.5 ± 4.2 μm along the transverse direction (TD) compared with the as-received material. A weakened texture was also obtained in CoreFlowed AZ31B, with basal poles aligned parallel to TD shift toward extrusion direction (ED) from wire center to edge. Periodic needle-like regions with a distinctively different orientation from neighbouring regions were observed at the sample edge. The engineering ultimate tensile strength (UTS) and elongation (El) of the CoreFlowed sample was 258 ± 5 MPa and 22.3 ± 0.8%. The El was significantly increased by 58% with equivalent UTS compared to the as-received material. Such a good combination of strength and ductility is attributed to grain refinement with heterogeneity, texture weakening, and homogeneously redistributed second phase particles. Graphical abstract: Image, graphical abstract